Interpretation of SAP2000 Analysis Results Using the Design Response Spectrum Method in Earthquake Resistance in the Structural Performance of High-Story Buildings According to SNI 1726:2019 - Reja Andika; Tira Roesdiana (Riviera Publishing, 2025)
This research investigates earthquake dynamics and their impact on structural responses, focusing on building flexibility and rigidity’s influence on seismic performance. Using SAP2000 version 24 software as per 1726:2019 guidelines, the KC BTN Bank office building in Cirebon was evaluated. Seismic load data from RSA PuSGeN Cipta Karya (Desain Spektra Indonesia 2021) assessed the structure's safety against Indonesian seismic standards. The analysis confirms compliance, achieving safety limits and a 90% modal participation mass ratio per Article 7.9.1 of SNI 1726:2019. The building's fundamental periods (T) are 0.562 seconds (Tc) and 0.546 seconds (Ta Min) for each direction. Base reactions reached a 100% scale factor, meeting Article 7.9.1.4.1 requirements. Story displacements in the X and Y directions due to lateral sway are safe, with drifts below the allowable values in Table 20 of SNI 1726:2019. The findings show that the structural design meets earthquake-resistance requirements, ensuring safety and compliance. This research underscores the need for thorough design reviews, confirming that main structural elements align with criteria for multi-story buildings, and provides insights for optimizing designs to enhance resilience and safety in seismically active regions.